The Effect of Profitability, Liquidity, Growth Potential, and Managerial Ownership on Dividend Policy - Erliana; Linawati; Hakim, Lukmanul; Rizkiyani, Ika (IJESS International Journal of Education and Social Science, 2025)
This study aims to examine the influence of profitability (ROA), liquidity (Current Ratio), growth potential, and managerial ownership on dividend policy in energy sector companies listed on the Indonesia Stock Exchange during the period 2020–2024. A quantitative research approach was applied using panel data from annual financial reports. The dependent variable, dividend policy, is proxied by Dividend per Share (DPS), while the independent variables include ROA, CR, growth potential, and managerial ownership. The data analysis method employed is multiple linear regression using the Fixed Effect Model (FEM). The findings reveal that profitability and managerial ownership significantly affect dividend policy, indicating that companies with higher profitability and greater ownership by management are more likely to distribute dividends. On the other hand, liquidity and growth potential do not show a significant relationship with dividend policy. These results suggest that internal financial strength and the alignment of interests between management and shareholders are key determinants of dividend decisions in the energy sector. This study contributes to a deeper understanding of dividend policy determinants and offers practical implications for investors, company executives, and policymakers.